Plataforma integral para seguimiento en tiempo real de un prototipo de bombas de infusión peristáltica, Universidad Privada del Valle, Cochabamba, Bolivia - Martínez Montes de Oca, Keyla Mey (2025)
Objective: To design and implement a comprehensive platform for the real-time tracking, traceability, and monitoring of infusion pumps, incorporating a prototype of a peristaltic infusion pump, with the purpose of optimizing intravenous therapy monitoring and enhancing the efficiency of medical and nursing staff. Materials and methods: A prototype of a peristaltic infusion pump was developed using 3D printing, a method that enables the precise and customized creation of highly durable and functional components. The prototype integrates microcontrollers and sensors capable of detecting anomalies during drug administration, ensuring constant flow control. In parallel, a digital platform was designed with access through a web interface, allowing continuous real-time monitoring of the pumps. This low-cost solution, developed in Bolivia, aims to facilitate implementation in settings where existing commercial systems—although technologically advanced—are less accessible due to their high cost. The proposed system centralizes supervision and optimizes medical staff resources. Results: A series of experimental tests were conducted to evaluate the prototype’s accuracy compared to standard commercial infusion pumps by analyzing the percentage error in infusion rates. The prototype achieved an acceptable error range between -2.68 % and +2.57 %, demonstrating its accuracy and functionality. Furthermore, the digital platform proved effective in optimizing monitoring time, enabling healthcare personnel to focus on higher-priority tasks. Conclusions: The implementation of this comprehensive platform and the first prototype of a peristaltic infusion pump marks a significant step forward in intravenous therapy monitoring in Bolivia. Its low-cost design makes it a viable alternative for expanding access to real-time monitoring, promoting technological innovation, and optimizing both human and material resources in hospital settings.